Contract administration / Diyanah Abdul Gani - Abdul Gani, Diyanah (Universiti Teknologi MARA, Perak, 2015)
Contract administration is very important thing to elaborate, therefore this report will discuss about procedures for contract administration based on DID Manual 2009. This report explained more detail about Pre-Contract, Contractual Stage and Post-Contract. However, elaborate how to fullfill the requirements in the guidelines. It will focus to the Owner and Consultant not only to determine that the work is proceeding in conformity with the contract documents, but also because it allows a final opportunity to detect any inaccuracies, ambiguities or inconsistencies in the design. Hence, all the standard procedures of DID manual to ensure duration of preparing all the documents complete on time. Then, this report will also look at the common mistakes made contractor upon submission of tender that can cause wasting of time and cost.